Surgical Care in Specialist Ophthalmology Departments: Structure and Impact of the COVID-19 Pandemic - Karaca, Olga; Agostini, Hansjürgen; Bialas, Enno; Hahn, Ursula; Neubauer, Aljoscha S.; Rüggeberg, Jörg-Andreas; Subert, Janine; Ziemssen, Focke (Klinische Monatsblätter für Augenheilkunde, 2022)
Background Specialist ophthalmology departments contribute to the surgical care of German patients. Outpatient and inpatient surgeries were restricted during the COVID-19 pandemic and led to a sharp decline in the number of cases in ophthalmological care. The aim of this analysis was to improve the understanding of the logistic structures of medical facilities as well as the effects of the pandemic.Material and Method Based on reported process data, a sample of the specialist ophthalmological departments were examined based on operation and procedure codes (OPS) and data submitted between 01.01.2017 and 31.05.2021 according to the benchmarking programmes of the Professional Association of German Anaesthetists (BDA), the Professional Association of German Surgeons (BDC), and the Association for Operating Theatre Management (VOPM).Results Eighteen ophthalmology departments from Germany were analysed. After the decline in the number of cases (by temporarily up to 48%) during the first wave of the pandemic, the case numbers of all interventions assessed as nonurgent continued to be reduced. While intravitreal injections hardly decreased during the first wave (− 16%), significant drops in the coverage of cataract surgery (− 79%), vitrectomies (− 35%), glaucoma surgery (− 59%), strabismus surgery (− 95%), and eyelid surgery (− 52%) were found. One exception was intravitreal injection, which stabilised at a lower level early on during the pandemic. Overall, the number of cases during the later phases of the pandemic were significantly reduced below the level of previous years, despite the maintenance of emergency care. The underuse was variable for different interventions.Conclusion In addition to self-reported figures, the analysed process data demonstrates the effect that various factors had on elective as well as urgent operations within hospital care during the pandemic. Despite partial stabilisation of some services, a relevant supply gap for outpatient and inpatient interventions was identified, with corresponding effects on the eye health of the population, while compensation or performance enhancement have not taken place to date. Facing the growing preload and the demographic development, future structures must therefore allow for an increase in the performance of specialist ophthalmological departments.
Keywords: COVID-19 pandemic; caseload development; intravitreal injection; IVI